Pengaruh Locus of Control dan Disiplin Kerja terhadap Kinerja Karyawan pada CV Klasindo Plafon PVC - Malau, Mestika Lestari; Muttaqin, Ridlwan; Aryanti, Asti Nur (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This research examines the influence of locus of control and work discipline on employee performance at CV Klasindo Plafon PVC. This research uses multiple linear regression analysis and involves a population of 35 employees. Employee performance is the dependent variable, while the independent variables are the locus of control and work discipline. The aspects of employee performance cover the amount of work produced, the quality of that work, punctuality, attendance, and teamwork skills. Locus of control is divided into internal and external. Work discipline encompasses effective time management, task accountability, and attendance records. Data was collected using observation and questionnaires. Various statistical methods, such as partial hypothesis testing, simultaneous analysis, and coefficient of determination, shall be used in the analysis. The research results show that locus of control and work discipline positively and significantly affect employee performance individually and collectively